Digital Media Literacy Strategy for the Information Disruption Era in Improving the Communication Ethics of the Yogyakarta Community - Sintar Nababan (GoAcademica Research & Publishing, 2023)
Social media users in Indonesia continue to increase. In 2022, active users of social media in Indonesia according to the research from Hootsuite reach 191,4 million people, increased by 12,6% from 2021. According to the research from Microsoft in 2020, Indonesian Netizen’s digital politeness is in ranked 29th of the 32 countries. To deal with disruption of information, good digital literacy is needed. According to research results from the Ministry of Communication and Informatics in 2021 and 2022, province that has highest digital literacy rate in Indonesia is the Special Region of Yogyakarta. Therefore, researcher choose that as a research subject. This research aim to know literacy media digital Strategy of Communication and Informatics Office of the Special Region of Yogyakarta to increase communication ethics of people, reviewed from the aspect of accessing, evaluating, and producing content. The research method used is qualitative. The results of this study are that the Communication and Informatics Office of the Special Region of Yogyakarta has awareness, responsibility, integrity or honesty, and benevolence in accessing, evaluating, and producing content. Implementation of the Strategy for the Communication and Informatics Office of the Special Region of Yogyakarta is through the Positive Content Dissemination Program, Education through Digital Media, Digitization Training, and Short Film.